Exploring ethnomathematics in the traditional houses of Tamarele, Buano Utara village, as a source of mathematics learning - Ratau, Asria; Cholily, Yus Mochamad; Rahardjanto, Abdulkadir; Effendi, Moh. Mahfud; Inganah, Siti (Universitas Islam Negeri Raden Intan Lampung, 2025)
Mathematics is often considered an abstract science far removed from real life. The ethnomathematics approach aims to link mathematical concepts with local cultural practices. This study aims to explore the mathematical elements in the traditional houses of Hena Puan in Buano Utara Village and examine their potential as a source of mathematics learning. The method used is qualitative with an ethnographic approach. Data was collected through observation, interviews with traditional leaders, and visual documentation of the traditional house structure. The study results show that the Hena Puan traditional house contains mathematical concepts such as plane and solid geometry. Additionally, philosophical values related to the structure of the building, which have been passed down from generation to generation, were found. The implications of these findings suggest that the Hena Puan traditional house can serve as a relevant contextual learning resource, encourage student engagement, and strengthen local cultural identity. The implications of this study can be used as a source of contextual learning that makes mathematics learning more concrete, meaningful, and relevant to students' lives.